Penerapan Arsitektur Tropis pada Perancangan Sekolah Khusus Olahraga Berstandar Internasional di Pandeglang Banten - Iffah Nur Syafiqoh; Harfa Iskandaria (MAESTRO, 2019)
Abstract The Sports School is a school founded with the aim of developing young talents in the field of sports but can also carry out the task their duties as students in general. This school provides standard International facilities, ranging from the size of the field to the material used in the facilities. This development plan seeks to provide a building function that accommodates teaching and learning activities and training with international standard with a tropical architectural approach. The theme of tropical architecture that is applied aims to unite climate conditions in Indonesia with their application to site and buildings. Keyword: The Sports School, International Standard, Tropical Architecture